Exciton spectrum in multi-shell hexagonal semiconductor nanotube - Makhanets, O.M.; Gutsul, V.I.; Tsiupak, N.R.; Voitsekhivska, O.M. (Condensed Matter Physics, 2012)
The theory of exciton spectrum in multi-shell hexagonal semiconductor nanotube is developed within the effective masses and rectangular potentials approximations using the method of effective potential. It is shown that the exciton binding energy for all states non-monotonously depends on the inner wire diameter, approaching several minimal and maximal magnitudes. The obtained theoretical results explain well the experimental positions of luminescence peaks for GaAs/Al₀.₄Ga₀.₆As nanotubes. У наближеннi ефективних мас та прямокутних потенцiалiв, з використанням методу ефективного потенцiалу побудовано теорiю екситонного спектра у складнiй багатошаровiй шестиграннiй напiвпровiдниковiй нанотрубцi. Отриманi теоретичнi результати добре пояснюють експериментальнi положення пiкiв люмiнесценцiї у нанотрубках GaAs/Al₀.₄Ga₀.₆As.